2004
DOI: 10.1002/jbm.a.30204
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cytocompatibility and bending modulus of nanoceramic/polymer composites

Abstract: In an attempt to simulate the microstructure and mechanical properties of natural bone, novel nanoceramic/polymer composite formulations were fabricated and characterized with respect to their cytocompatibility and mechanical properties. The bending moduli of nanocomposite samples of either poly(L-lactic acid) (PLA) or poly(methyl methacrylate) (PMMA) with 30, 40, and 50 wt % of nanophase (<100 nm) alumina, hydroxyapatite, or titania loadings were significantly (p < 0.05) greater than those of pertinent compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(52 citation statements)
references
References 15 publications
0
49
0
1
Order By: Relevance
“…Previous studies have shown that the presence and size of nanoscale features on a material surface affect protein interactions [1] and thus subsequently modulate the functions of different cell types in specific manners [1,2]. For example, osteoblast adhesion is selectively enhanced on nanophase alumina, titania, and hydroxyapatite while fibroblast adhesion is suppressed on these materials [3].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the presence and size of nanoscale features on a material surface affect protein interactions [1] and thus subsequently modulate the functions of different cell types in specific manners [1,2]. For example, osteoblast adhesion is selectively enhanced on nanophase alumina, titania, and hydroxyapatite while fibroblast adhesion is suppressed on these materials [3].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the select preference and specific enhanced adhesion of osteoblasts was maintained only on composites of poly (L-lactic) acid (PLA) and nanophase (but not on polymer/conventional) ceramics (alumina, titania and hydroxylapatite) composites [4]. Specifically, osteoblast adhesion on the 50:50 (w:w)% PLA/nanophase alumina composite was similar to that obtained on 100% nanophase ceramic (the maximum observed in the study) In addition, these material formulations exhibited improved mechanical (specifically, bending modulus) properties [4].…”
Section: Cell Adhesionmentioning
confidence: 99%
“…19 Specifically, compared with a bending modulus of 60 ± 3 MPa for plain PLA and 870 ± 30 MPa for conventional titania/PLA composites with a weight ratio of 50/50, the bending modulus of nanophase titania/PLA composites with a weight ratio of 50/50 was 1960 ± 250 MPa. 19 In the paper, 19 the ceramic nanoparticles of varying amounts (30,40, and 50 wt%) were simply mixed with the polymers in organic solvents to compare the effect of the weight percentage of particles on the mechanical properties of the composites. The dispersion status of the nanoparticles was, however, not addressed.…”
Section: Introductionmentioning
confidence: 95%
“…17,18 Indeed, greater mechanical properties have been reported for polymer composites with a reduction in ceramic grain size into the nanometer range. 19 For example, McManus et al reported that the bending moduli of composites of PLA with 40 and 50 wt% nanophase (,100 nm) alumina, titania and HA were significantly greater than respective composite formulations with conventional coarser grained ceramics. 19 Specifically, compared with a bending modulus of 60 ± 3 MPa for plain PLA and 870 ± 30 MPa for conventional titania/PLA composites with a weight ratio of 50/50, the bending modulus of nanophase titania/PLA composites with a weight ratio of 50/50 was 1960 ± 250 MPa.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation